Analysis of morphological, morphokinetics, cell-free DNA, microRNAs parameters to predict aneuploidy status of embryos - Achmad Kemal Harzif; Intan Indah Permatasari; Patricia Alika Kurniawan; Thalia Amila Elsiyana; Fistyanisa Elya Charilda; Azizah Fitriayu Andyra; Heidi Dewi Mutia; Nafi’atul Ummah; Putri Nurbaeti; Amalia Shadrina; Pritta Ameilia Iffanolida; Kresna Mutia; et al. (PLoS ONE, 2026)
Background In Vitro Fertilization (IVF) is one of the most effective infertility treatments. Preimplantation genetic testing for aneuploidy (PGT-A) is invasive, high-cost, and has the potential risk of embryo damage. Our study explores noninvasive approaches to assess embryo quality through morphology and morphokinetics and analyze miRNA, cell-free DNA (cfDNA) for embryo chromosomal status. Methods This cross-sectional study followed the STROBE guideline. We analysed the relationship between embryo morphology, morphokinetics, cfDNA, and microRNAs with the aneuploidy status of day-5 embryos at the blastocyst stage. Non-probability consecutive sampling yielded 124 embryos between 28th December 2021 and 31st December 2022 in our center. Model performance was evaluated using the area under the curve (AUC) from receiver operating characteristic (ROC) analysis. Results Of 124 embryos, 50.8% had aneuploid chromosomes. Analysis of ccfDNA demonstrated a significantly higher rate of aneuploidy from aneuploid embryos compared to the euploid group (p < 0.001). Morphokinetic parameters assessment showed longer pronuclear fading time (21.9 vs. 19.9 hours; p = 0.041) and shorter third cell cycle synchrony (13.4 vs. 17.5 hours; p = 0.036). The expression of miRNA-191 and miRNA-372 was higher in aneuploid compared to euploid embryos (8.1 fold, p < 0.001, and 6.5 fold, p = 0.008, respectively). ROC analysis revealed predictive values for miRNA-191 (AUC 0.745, sensitivity 73%, specificity 70.5%) and miRNA-372 (AUC 0.638, sensitivity 68.3%, specificity 55.7%). MiRNA-191, expansion category, and noninvasive PGT-A (niPGT-A) were identified as independent predictors of embryo ploidy status (p = 0.005). Conclusion Embryo chromosomal status can be evaluated by integrating morphology, morphokinetics, miRNA-191, miRNA-372, and cell-free DNA.